PENGEMBANGAN MEDIA FUN THINKERS BOOK PADA PEMBELAJARAN IPAS KELAS III DI SD NEGERI TANAH MERAH - Rahmi Fitri, Fathiyya; Sukirno; Aprilia, Rapita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is that science learning is still centered on the delivery of material by the teacher so that students are not actively involved in the learning process of natural and artificial appearances material. The purpose of this study is to determine the development process, expert validation, practicality, and effectiveness of the Fun Thinkers Book media. The method used in this study is Research and Development (R&D) with the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were 13 thirdgrade students of Tanah Merah State Elementary School. Data collection instruments include observation sheets, interviews, validation questionnaires (material, language, and media experts), teacher and student response questionnaires, and pretest and posttest tests. The results of the study showed a 100% validation of the material with a “very high” criterion, 92% with a “very high” criterion for linguists, and 100% with a “very high” criterion for media experts. In the implementation phase, the teacher response rate was 94% with a “very practical” criterion, and the student response rate was 92.30% with a “very practical” criterion. The trial results showed that the N-Gain value for the pretest and posttest was 0.82 with a “high” criterion, and the N-Gain percentage was 81.67% with an “effective” criterion. It is recommended that schools with this media development will increase student enthusiasm, teachers are expected to be able to use the media, and future researchers are expected to continue developing the media with more diverse variations.